Environmental study of the variety variety apple cultivation, in the middle and lower basins of the Mala River, Cañete – Peru - Figueroa Vásquez, Carmen del Pilar (2019)
This study is located geographically in the Mala river basin, in the department of Lima, to determine to what extent the climatic, physical and social factors influence the development of the production of the Delicia variety apple, the main crop in the basin middle and low of the Mala river? The objective is to determine the ranges of temperatures and relative humidity, as well as the main physical and social conditions. The average annual temperature in the meteorological stations located in the areas of Delicia apple production in the Mala river basin are 20.83 ° C, 21.48 ° C and 17.10 ° C, the referred parameter is given in the range of 13 ° C to 21 ° C established in other apple producing areas in the world for the vegetative development of the crop; while the average annual relative humidity of 82.05%. In reference to the physical characteristics, the apple orchards are developed in the flat lands of the valley, the soil characteristics correspond to medium-quality soils for agricultural activity, being poor in organic matter, with a pH of lightly to moderately alkaline and with low CIC values. The farmers dedicated to the production are in their majority an aged population, with senescent families whose children became independent, they are educated people with secondary or technical / superior; in the production of apple, the orchards smaller than one hectare predominate.